Left Ventricular Assist Device Implantation and Concomitant Dor Procedure: a Single Center Experience - Schaefer,Andreas (2020)
Abstract Objective: Left ventricular assist device (LVAD) implantation with concomitant Dor plasty is only reported anecdotally. We herein aimed to describe our experience with LVAD and concomitant Dor procedures and describe long-term outcomes of this special subset of heart failure patients. Methods: Between January/2010 and December/2018, 144 patients received LVAD therapy at our institution. Of those, five patients (80% male, 60.4±7.2 years) presented with an apical aneurysm and received concomitant Dor plasty. Apical aneurysms presented diameter between 75 and 98 mm, with one impending rupture. Results: Procedural success was achieved in all patients. No unplanned right ventricular assist device implantation occurred. Furthermore, no acute 30-day mortality was seen. In follow-up, one patient was lost due to intentional disconnection of the driveline. One patient underwent heart transplantation on postoperative day 630. The remaining three patients are still on device with sufficient flow; pump thromboses were successfully managed by lysis therapy in one patient. Conclusion: LVAD implantation with concomitant Dor procedure is feasible, safe, and occasionally performed in patients with ischemic cardiomyopathy. Major advantages are prevention of thromboembolism and facilitation of LVAD placement by improving pump stability and warranting midventricular, coaxial alignment of the inflow cannula. In long-term follow-up, no adverse event associated with Dor plasty was observed.